The SINS in Business Negotiations: Explore the Cross-Cultural Differences in Business Ethics Between Canada and China - Ma, Zhenzhong (Journal of business ethics, 2010)
Ethical dilemmas are inescapable components of business negotiations. It is thus important for negotiators to understand the differences in what is ethically appropriate and what is not. This study explores the cross-cultural differences in business ethics between Canada and China by examining the perceived appropriateness of five categories of ethically questionable strategies often used in business negotiations. The results show that the Chinese are more likely to consider it appropriate to use ethically inappropriate negotiation strategies, but the impact of cultural values on ethically inappropriate negotiation strategies is much stronger in Canada than in China when negotiators choose to use these strategies. In addition, there are more gender differences in Canada, where men are more likely to consider it appropriate to use ethically questionable strategies in all five categories than women; while in China no gender differences are found in the perceived appropriateness of using these strategies in all but one category. Implications are also discussed along with potential future research directions.